Natural Head Posture in the Setting of Sagittal Spinal Deformity: Validation of Chin-Brow Vertical Angle, Slope of Line of Sight, and McGregor's Slope With Health-Related Quality of Life. Issue 1 (July 2016) - Lafage, Renaud; Challier, Vincent; Liabaud, Barthelemy; Vira, Shaleen; Ferrero, Emmanuelle; Diebo, Bassel G.; Liu, Shian; Vital, Jean-Marc; Mazda, Keyvan; Protopsaltis, Themistocles S.; Errico, Thomas J.; Schwab, Frank J.; et al.
Abstract : BACKGROUND: The maintenance of horizontal gaze is an essential function of upright posture and global sagittal spinal alignment. Horizontal gaze is classically measured by the chin-brow vertical angle (CBVA), which is not readily measured on most lateral spine radiographs. OBJECTIVE: To evaluate relations between CBVA and the slope of the line of sight, the slope of McGregor's line (McGS), and Oswestry Disability Index. METHODS: Patients were identified from a single center database of 531 spine patients who underwent full-body EOS x-rays. Correlations between CBVA, the slope of the line of sight, and McGS were assessed. Using a quadratic regression with Oswestry Disability Index and CBVA, windows of low disability were identified. Comparison of sagittal spinopelvic parameters was carried out between patients with "ascending gaze" and "neutral position." RESULTS: Three hundred three patients were included (74% female, mean age 54.8 years, body mass index 26.6 ± 6.0 kg/m 2 ). CBVA strongly correlated with the slope of the line of sight (r = 0.996) and McGS (r = 0.862). Regression studies between Oswestry Disability Index and CBVA yielded a range of values corresponding to low disability (−4.7 degrees to 17.7 degrees). Similarly, a low disability range for the slope of the line of sight (−5.1 degrees to 18.5 degrees) and McGS (−5.7 degrees to 14.3 degrees) was computed. Patients with "ascending gaze" had a worse spinopelvic alignment than "neutral position" patients. CONCLUSION: The slope of the line of sight and McGS correlated strongly with CBVA and can be used as surrogate measures. The range of values for these measures corresponding to low disability was identified. These values can be used as a general guideline to assess alignment for diagnostic purposes. Cervical compensatory mechanism may modify the natural head position in sagittally misaligned patients. ABBREVIATIONS: CBVA, chin-brow vertical angle HRQoL, health-related quality of life McGS, slope of McGregor's line ODI, Oswestry Disability Index SLs, slope of the line of sight